Optical system to observe an measure the spectra of a light emitting substrate and plasma in a RF magnetron - Andreas Lich, Julian (Pontificia Universidad Católica del Perú, 2017)
To obtain spectra of a light emitting substrate during the deposition of Terbium (Tb) doped thin films by RF magnetron sputtering, an optomechanical device is developed, constructed and tested. The device is required to enable spatial scans of the substrate plane and the plasma beneath. Thereby, measurements of spatial emission intensity distribution and a separation of the Tb spectrum from the plasma-overlain substrate spectrum shall be possible. After an introduction into theoretical and practical boundary conditions, the system’s requirements are specified, followed by a brief investigation of existing solutions for similar problems. A basic optical prototype system is introduced and analysed. After a discussion and evaluation of part solutions, an optomechanical system is developed, constructed, analysed and compared to the prototype system.

Zur spektralen Analyse eines lichtemittierenden Substrates während des Beschichtungsprozesses von Terbium (Tb)-dotierten Dünnfilmen durch RF Magnetronsputtern wird ein optomechanisches Gerät entwickelt, konstruiert und getestet. Das Gerät soll räumliche Scans der Substratoberfläche und dem, sich darunter befindenden, Plasma ermöglichen. Räumliche Verteilungen der Emissionsintensit ät sollen dadurch messbar- und das Tb-Spektrum von dem plasmaüberlagerten Substratspektrum trennbar gemacht werden. Nach einer Einführung in die theoretischen- und praktischen Rahmenbedingungen erfolgt die Präzisierung der Aufgabenstellung und eine kurze Recherche zu bereits vorhandenen Lösungen von ähnlichen Problemen. Ein Prototyp wird vorgestellt und geprüft. Nach der Diskussion und Evaluierung von Teillösungen wird ein optomechanisches System entwickelt, konstruiert, analysiert und mit dem Prototyp verglichen.
Keywords: Optoelectrónica--Dispositivos electrónicos; Diseño de sistemas; https://purl.org/pe-repo/ocde/ford#2.00.00